Application of Game Theory Principles for Opportunistic Routing in MANETS - Mangadevi Atti; Manas Kumar Yogi (International Journal of Mobile Computing Technology, 2024)
This article explores the application of game theory principles to enhance opportunistic routing in mobile ad hoc networks (MANETs). MANETs are characterized by their dynamic topology, limited resources, and lack of infrastructure, making traditional routing protocols less efficient. Opportunistic routing leverages the mobility of nodes and the broadcast nature of wireless communication to achieve reliable message delivery. However, existing opportunistic routing algorithms may suffer from challenges such as high message loss rates and excessive overhead. By incorporating game theory principles, such as strategic decision-making and incentive mechanisms, into the routing process, this research aims to improve the performance and efficiency of opportunistic routing in MANETs. The proposed approach enables nodes to strategically decide when and where to forward messages based on their own utility functions, network conditions, and interactions with other nodes. Through simulation studies and performance evaluations, the effectiveness of the game theory–based opportunistic routing algorithm is demonstrated in terms of packet delivery ratio, end-to-end latency, and overhead reduction. The results highlight the potential of game theory to address the inherent uncertainties and dynamics of MANETs, leading to more robust and adaptive routing solutions.
Keywords: Game theory; congestion; mobile ad hoc networks (MANETs); network traffic; routing